An analysis of mitochondrial variation in cardiomyopathy patients from the 100,000 genomes cohort: m.4300A>G as a cause of genetically elusive hypertrophic cardiomyopathy - Luis R. Lopes; William L. Macken; Seth Du Preez; Huafrin Kotwal; Konstantinos Savvatis; Neha Sekhri; Saidi A. Mohiddin; Renata Kabiljo; Robert D. S. Pitceathly (Human Genomics)
Abstract Background A significant proportion of cardiomyopathy patients remain genetically unsolved. Our aim was to use the large genomes cohort of the 100,000 genomes project (100KGP) to explore the proportion of potentially causal mitochondrial (mtDNA) variants in cardiomyopathy patients, particularly in genotype-elusive participants. The homoplasmic MT-TI 4300A>G is unusual in that it typically presents with a cardiac-only phenotype, but MT-TI is currently not part of the genes analysed for non-syndromic cardiomyopathies. Results We analysed 1363 cardiomyopathy genomes from the 100KGP project (of which only 172 had been previously solved) to detect disease causing mtDNA variants. MitoHPC was used to call variants. For controls, 1329 random subjects not recruited for a cardiomyopathy diagnosis and not related to any participant in the cardiomyopathy cohort were selected. We have additionally compared the frequency of detected variants with published UK Biobank data. Pathogenicity annotations were assigned based on MitoMap. Four patients, all with a diagnosis of hypertrophic cardiomyopathy (HCM) and without a previously identified genetic cause from the 100KGP clinical-standard analysis, were found to harbour the pathogenic MT-TI m.4300A>G variant (0.6% of HCM cases without a diagnosis). Conclusion These data support the inclusion of MT-TI in the initial genetic testing panel for (non-syndromic) HCM.